(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of e-cigarette use and its associated factors among students at Tay Thanh High School, Tay Thanh Ward, Tan Phu District, Ho Chi Minh City, in 2024. Subjects and Methods: A cross-sectional study was conducted to assess the prevalence of e-cigarette use and related factors among students currently enrolled at Tay Thanh High School, Tan Phu District, Ho Chi Minh City, in 2024. Results: Among 521 participating students, the 30-day prevalence of current e-cigarette use was 1.92%. Additionally, 4.4% reported an intention to try e-cigarettes. Factors significantly associated with e-cigarette use included sex, alcohol consumption, parental respect, weekly pocket money, exposure to e-cigarette advertising through media (predominantly social media and the Internet), secondhand smoking exposure, and a physically inactive lifestyle. Conclusion: The prevalence of current e-cigarette use among students at Tay Thanh High School was relatively low and was associated with individual, family, and school-related factors. Social media and the Internet were the most commonly accessed communication channels. These findings suggest that e-cigarettes are increasingly reaching students, highlighting the need for appropriate control and regulatory strategies.